INTEGRATING ENGLISH INTO P5 PROGRAM OF MERDEKA CURRICULUM AT SMP NEGERI SATAP 2 SANGALLA’ - Betteng, Ira Sulistina; Patanduk, Sushy Teko; Ba’ka, Charlie (Teaching English as a Foreign Language Overseas Journal, 2025)
The objective of this research is to find out how the English teacher integrating English into P5 program of Merdeka Curricullum at SMP Negeri Satap 2 Sangalla'. The researcher conducted this research used qualitative methods. Purposive sampling strategies were used to acquire data from two (2) English teacher. The data obtained from observation and interview then analyze descriptive. The result of this study show how the English teacher integrating English into P5 program at SMP Negeri Satap 2 Sangalla’. The findings show that there is learning planning, use of English learning object, and learning process in P5 activities. The conclusion is that the researcher found that English was properly integrated into P5 activities starting from planning, English learning objects, to the steps of the learning process.